2022
DOI: 10.1177/09612033221140724
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids: Current insights into mechanisms of action in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is one of the autoimmune diseases characterized by the lack of self-tolerance and the formation of immune complexes and nuclear autoantigens resulting in inflammation in multiple organs. Nowadays, the major aim of SLE therapy is the control of disease activity. However, the biological heterogeneity between patients and the absence of safe and specific targeted treatments complicate the lupus management. Therefore, the potential prophylactic effects of natural therapy consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 124 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…Finally, PUFA supplements, in particular omega-3, may be an effective treatment for non-specific dry eye disease ( 35 , 36 ). Various mechanisms have been hypothesized to theorize why omega 3 fatty acids may improve outcomes associated with SLE, including by reducing disease activity, reducing inflammation, regulating adipokine production, and improving endothelial function ( 37 ). The use of high doses of omega-3 rich foods and oils as part of the recovery protocol is a novel test of this previous research in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PUFA supplements, in particular omega-3, may be an effective treatment for non-specific dry eye disease ( 35 , 36 ). Various mechanisms have been hypothesized to theorize why omega 3 fatty acids may improve outcomes associated with SLE, including by reducing disease activity, reducing inflammation, regulating adipokine production, and improving endothelial function ( 37 ). The use of high doses of omega-3 rich foods and oils as part of the recovery protocol is a novel test of this previous research in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation contributes to increased susceptibility to SLE by inducing inflammation and immune function change via upregulating multiple inflammatory mediators, interacting with the glutathione S-transferase Mu 1 (GSTM1) null genotype that clear reactive oxygen intermediate more slowly and therefore have more oxidative stress, and increasing the expression of nuclear autoantigens on the keratinocyte surface via triggering DNA damage [ 43 , 45 ]. Plausible mechanisms of ω-3 PUFAs’ anti-inflammatory property include decreasing the generation of inflammatory mediators like prostaglandins (PGs) by competing with ω-6 PUFAs, suppressing pro-inflammatory cytokine production, and inhibiting the proliferation and function of multiple immune cells [ 16 , 46 ]. Therefore, a possible explanation for our interesting finding is that fish oil supplementation partly blocks the harmful effects of UV radiation in females on SLE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis revealed the significant potential of unsaturated fatty acids in the management of SLE, particularly with regard to regulating disease activity and improving lipid profiles. UFAs, especially omega-3 and omega-6 polyunsaturated fatty acids (PUFAs), are known for their anti-inflammatory properties, which may help suppress SLE disease activity [ 15 , 36 ]. Our findings align with previous studies showing that omega-3 fatty acids have beneficial effects on various rheumatic diseases, including SLE [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%